Analisis Arahan Penggunaan Lahan berdasarkan Kelas Kemampuan Lahan di Daerah Aliran Sungai Kelep Lombok: Analysis of Land Use Direction based on Land Capability Class in the Kelep Watershed, Lombok - Endah Herlina; Hayati Hayati; Muktasam Muktasam (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
Conversion of forest land into agricultural land is a serious concern in the Kelep watershed. Agricultural methods applied without proper application of soil preservation and agrotechnology have resulted in significant erosion and reduced land productivity. Efforts to manage the Kelep watershed must be carried out by combining the interests of soil and water conservation with increase in agricultural production. The first step is to evaluate the capability of the land in this area. The aim of this study is to formulate a direction for land use for sustainable corn-based agriculture according to its capability class in the Kelep watershed. The results showed that the Kelep watershed was dominated by land with class IV 5,335.3 ha (48.02%) and VI 3,493.04 ha (30.95%) and III 1,813.71 ha (16. 32%) with the inhibiting factors for all land capability classes being the sensitivity of soil erosion (low-medium-rather high), slopes (wavy-wavy-slightly steep), and erosion damage (medium-rather heavy and heavy). Land with ability classes II, III and IV, can be utilized for the cultivation of Corn Plants (Zea Mays), accompanied by the application of agrotechnology and proper soil and water conservation so that it is sustainable, while land in class VI is not suitable for Corn cultivation, preferably for vegetation. permanent or forest in combination with the development of understorey plants with agroforestry patterns.